2021
DOI: 10.3390/ijms22179537
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric and Fibrillar Species of Aβ42 Diversely Affect Human Neural Stem Cells

Abstract: Amyloid-β 42 peptide (Aβ1-42 (Aβ42)) is well-known for its involvement in the development of Alzheimer’s disease (AD). Aβ42 accumulates and aggregates in fibers that precipitate in the form of plaques in the brain causing toxicity; however, like other forms of Aβ peptide, the role of these peptides remains unclear. Here we analyze and compare the effects of oligomeric and fibrillary Aβ42 peptide on the biology (cell death, proliferative rate, and cell fate specification) of differentiating human neural stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…We were able to determine this in vitro showing a relevant decrease of TUJ1 immunostaining after treatment with sarkosyl-insoluble fractions of P301S +/− or AD, and in vivo . The negative effect of amyloid fibrils, prefibrils vs oligomeric forms in cell survival has been described for several amyloids including Aβ [15], insulin fibers [6], lysozyme fibrils [66] see also ([24] for additional examples and review) using several protocols and experimental approaches. In fact, although a clear consensus is still elusive, brain-derived sarkosyl-insoluble fractions might contain different forms of tau fibrils [80] that can interact with cellular membranes leading to membrane instability and increased toxicity (see [24] for review).…”
Section: Discussionmentioning
confidence: 99%
“…We were able to determine this in vitro showing a relevant decrease of TUJ1 immunostaining after treatment with sarkosyl-insoluble fractions of P301S +/− or AD, and in vivo . The negative effect of amyloid fibrils, prefibrils vs oligomeric forms in cell survival has been described for several amyloids including Aβ [15], insulin fibers [6], lysozyme fibrils [66] see also ([24] for additional examples and review) using several protocols and experimental approaches. In fact, although a clear consensus is still elusive, brain-derived sarkosyl-insoluble fractions might contain different forms of tau fibrils [80] that can interact with cellular membranes leading to membrane instability and increased toxicity (see [24] for review).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, there could be the possibility that aggregated forms of Aβ peptide (as oligomers and fibrils) could mediate some of the observed cellular effects. In previous studies, we demonstrated that the Aβ42 peptide, in its oligomeric and fibrillar state, affects the phenotypic specification of hNSCs [ 44 ]. However, in the current work, aggregated forms of Aβ peptide have not been detected, although we cannot exclude the possible effects of soluble Aβ peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides released by cleavage at the γ-site are then free to undergo oligomerization and subsequent fibrillation to form the characteristic plaques found in the atrophic brains of AD patients. Aβ 42 is considered more toxic because it is more prone to oligomerization and this enhances its ability to exert neurotoxic actions ( 40 ). Additionally, according to recent research, the accumulation of CTF-99 stimulates an excessive alteration in the morphology of mitochondria leading to increased production of ROS, further contributing to their abnormal function and the progression of disease ( 41 ).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%